Aging and Migration in a Transition Economy: The Case of China - Örn B. Bodvarsson; Jack W. Hou; Kailing Shen (Institute for the Study of Labor (IZA), 2014)
Post-reform China has been experiencing two major demographic changes, an extraordinary amount of internal migration and an aging population. We present a general migration model which captures the idea that older migrants have shorter durations in the destination but possibly larger general human capital to transfer. Therefore, the incentive to migrate is ambiguously related to age. We test the theoretical implication using an extended modified gravity model, nuanced to fit the case of a transition economy. We find that shifts in China's age distribution have generated significant changes in the country's migration patterns.
Keywords: J61; J11; 330; internal migration; age distribution; reforms